IMPLEMENTASI MEDIA LOTTO ANGKA UNTUK MENGEMBANGKAN KEMAMPUAN MENGENAL BILANGAN PADA ANAK KELOMPOK A1 DI RA KHADIJAH 50 SUMBERASRI - Zahrotul Mufidah; Imam Wahyono; Yuli Tri Andini; Eka Ramiati (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this study was to determine the implementation of number lotto media to develop the ability to recognize numbers in children in group A1 at RA Khadijah 50 Sumberasri for the academic year 2021/2022, supporting factors and inhibiting factors for implementing number lotto media to develop ability to recognize numbers in children in group A1 in RA. Khadijah 50 Sumberasri for the academic year 2021/2022. This type of research uses descriptive qualitative research. Data collection techniques using observation, interviews, and documentation. The data analysis technique used Miles and Huberman. As for the validity of the data using Source Triangulation. The results showed that the number lotto media was very effective in developing the ability to recognize numbers in children in indicator 1) the child was able to say/mention a sequence of numbers 1-10. 2) the child is able to number by pointing to objects (recognize the concept of numbers with objects 1-10). 3) the child is able to show the order of objects for numbers 1-10. 4) the child is able to connect/pair number symbols with objects 1-10. The stages carried out by the teacher include: 1) Planning. 2) Implementation. 3) Evaluation. Of the 17 students of class A1 RA Khadijah 50 Sumberasri overall everything has improved, 14 children are developing very well in each indicator, 2 children are developing as expected in almost every indicator, 1 child is starting to develop in almost all indicators.